2021
DOI: 10.3390/polym13223950
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Komagataeibacter xylinus Inoculum for Bacterial Cellulose Biosynthesis Using Magnetically Assisted External-Loop Airlift Bioreactor

Abstract: The aim of this study was to demonstrate the applicability of a novel magnetically assisted external-loop airlift bioreactor (EL-ALB), equipped with rotating magnetic field (RMF) generators for the preparation of Komagataeibacterxylinus inoculum during three-cycle repeated fed-batch cultures, further used for bacterial cellulose (BC) production. The fermentation carried out in the RMF-assisted EL-ALB allowed to obtain an inoculum of more than 200× higher cellular density compared to classical methods of inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…For instance, one research group developed an external-loop airlift bioreactor in which they were able to achieve 200x higher cellular density than that of classical inoculum preparations. 174 In another modified version of the airlift reactor, the authors inserted porous plates inside a tubular reactor to diffuse an enriched oxygen supply. The research group found that the BC produced with this method had improved water-retention capabilities and enhanced Young's modulus.…”
Section: Vessels and Bioreactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, one research group developed an external-loop airlift bioreactor in which they were able to achieve 200x higher cellular density than that of classical inoculum preparations. 174 In another modified version of the airlift reactor, the authors inserted porous plates inside a tubular reactor to diffuse an enriched oxygen supply. The research group found that the BC produced with this method had improved water-retention capabilities and enhanced Young's modulus.…”
Section: Vessels and Bioreactorsmentioning
confidence: 99%
“…While the base design of the airlift may provide some advantage towards BC synthesis, specific requirements towards BC production necessitates some modifications of the reactor. For instance, one research group developed an external‐loop airlift bioreactor in which they were able to achieve 200x higher cellular density than that of classical inoculum preparations 174 . In another modified version of the airlift reactor, the authors inserted porous plates inside a tubular reactor to diffuse an enriched oxygen supply.…”
Section: Productionmentioning
confidence: 99%
“…Additionally, we found that our fundamental preparative work on high cell density K. xylinus cultivation strategies, which we started and proceeded in 2020, also crosses very recent and meaningful industrial progress. In this context, Zywicka et al 2021 presented a strategy to prepare high cell density K. xylinus culture broth for standardized inoculation of BNC producing processes under constant gassing and magnetic field stimulation in repeated fed batch airlift cultivation 49 . There, the authors report a drop of the dissolved oxygen to a final value of 2–3%.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of RMF has been shown to enhance the growth and metabolic activity of K. xylinus [118]. Furthermore, employing RMF-assisted bioreactors has led to an increase in BC yield compared to conventional static methods because they enhance both the quantity and quality of K. xylinus inoculum, consequently leading to a higher yield of the resulting BC [115]. However, the RMF application does not result in a higher incidence of cellulose non-producing mutants within the 72 h exposure period [119].…”
Section: Dynamic Bioreactormentioning
confidence: 99%